Case Report: Stepwise noninvasive diagnosis of Takotsubo cardiomyopathy in an elderly patient–From ECG clues to echocardiographic and CTA confirmation - Teng, Yanling; Sun, Xingxing; Wang, Minglang; Wang, Ziyang; Wang, Yilian (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTakotsubo cardiomyopathy (TTC) is frequently misdiagnosed as acute coronary syndrome in elderly patients. This case demonstrates how ECG findings facilitate a noninvasive diagnostic algorithm for TTC, validated by echocardiography and coronary computed tomography angiography (CCTA).Case summaryAn 88-year-old woman presented with chest tightness and dyspnea after emotional stress (bereavement). Initial ECGs showed the concurrent appearance of ST-segment elevations in anterior (V3-V5) and inferior leads (II, III, aVF), suggesting apical injury and the diagnosis of TTC. Bedside echocardiography revealed apical akinesis with preserved basal contraction (LVEF 35%), while CCTA ruled out obstructive disease. Supportive therapy led to symptom resolution. At 1-year follow-up, LVEF recovered to 61% with normalized ECG.ConclusionThis case highlights ECG's pivotal role in suspecting TTC, enabling a Noninvasive diagnostic approach (echocardiography + CCTA) for elderly patients.